PENGARUH ADITIF BaCO3 PADA KRISTALINITAS DAN SUSEPTIBILITAS BARIUM FERIT DENGAN METODA METALURGI SERBUK ISOTROPIK - Nugraha, Priska R.; Widanarto, Wahyu; Cahyanto, Wahyu Tri; Kuncoro, Handoko S. (BERKALA FISIKA, 2015)
Influences of concentration of BaCO3 on crystallinities and susceptibilities of barium ferrites using isotropic powder metallurgy method of fabrication is studied based on the characterization of X-Ray Diffraction (XRD), crystallite size distributions and hysteresis curve of Vibrating Sample Magnetometer (VSM). In this study, Fe2O3 of Cilacap iron sands are doped with BaCO3 with various concentrations of 15%, 30% and 45% at 1100 °C of sintering temperature. The results show that the addition of BaCO3 affects the formation of the multi-phase barium ferrite crystals and widen the crystallite size distribution, as well as lowering the saturations and the magnetic remanences. The optimum composition for barium ferrite magnets is obtained for 15% of BaCO3, with the highest mass susceptibility of 2.4 × 10-6 M3/Kg. Keywords: Barium hexaferrites, isotropic powder metallurgy, crystal characterizations, permanent magnets